Where shall wisdom be found?: wisdom in the Bible, the church and the contemporary world - Barton, Stephen C. (T&T Clark, 1999)
What is wisdom - and where is it to be found? A number of experts in a wide range of theological and related disciplines have come together to explore this question. In the first part they consider wisdom in Israel and in the church, drawing upon scriptural and historical sources, and case studies. In the second part theologians, philosophers, social scientists, ethicists and educationalists look at wisdom in the contemporary world. While much good work has been done on biblical traditions there has been very little on the many facets of wisdom in the Judaeo-Christian theological, philosophical and ethical traditions. This book breaks considerable new ground.